Anti-tumor Activity of Bufalin by Inhibiting c-MET Mediated MEK/ERK and PI3K/AKT Signaling Pathways in Gallbladder Cancer - Qian, Liqiang (J Cancer, 2020)
Gallbladder cancer is one of the most common malignant tumors in the biliary tract. In recent years, the chemotherapy treatment for gallbladder carcinoma has exhibited obvious characteristics of drug resistance and insensitivity, and one of the main factors is the existence of cancer stem cells. Here in this study, the effect of Bufalin on gallbladder cancer (GBC-SD) cells and the related mechanism were studied. The results indicated that Bufalin could inhibit the growth of gallbladder carcinoma both in vivo and in vitro. According to the biological behavior analysis, Bufalin induced apoptosis, inhibited the propagation, migration and invasion of GBC-SD cells, and blocked cell cycle at the G2/M stage. Besides, Bufalin inhibited the tumor sphere formation capability of gallbladder carcinoma in matrigel, reduced the expression of multiple stemness-associated proteins, including Oct4, Sox2 and the stem cell-surface marker proteins CD133 and CD44. Western blot assay showed that Bufalin inhibited MEK/ERK and PI3-K/AKT signaling pathways by inhibiting the expression of p-c-Met, which in turn affected the expression of apoptosis-related protein Mcl-1, and the invasion-associated proteins E-cadherin, MMP9 and Snail. Bufalin was found to have an inhibitory effect on the GBC-SD cell growth and reduce the self-renewal and characteristic of gallbladder cancer stem cells. It enhanced the chemotherapeutic sensitivity and reduced the metastasis of gallbladder carcinoma. In conclusion, Bufalin can be used as a new promising anticancer drug for gallbladder cancer patients who are resistant to traditional chemotherapy.